Mapping livestock value chains in the IGAD region - Guthiga, Paul M.; Karugia, Joseph T.; Massawe, Stella C.; Ogada, Maurice Juma; Mugweru, Lydiah; Ongudi, Silas; Mbo'o-Tchouawou, Michelle; Mulei, Leonard (Technical Centre for Agricultural and Rural Cooperation, 2017)
The study provides CTA with recommendations on the types of value chains to be supported and information on particular nodes that CTA could be involved in. It focuses on the IGAD region, which includes eight member states: Djibouti, Somalia, Eritrea, South Sudan, Sudan, Ethiopia, Uganda and Kenya, and on a select number of livestock commodity value chains. The study obtained data and information from ongoing and recently completed programmes.